2010
DOI: 10.1093/mp/ssp057
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Feedforward Control of the Expression of Folate Biosynthesis Genes in Tomato Fruit

Abstract: Little is known about how plants regulate their folate content, including whether the expression of folate biosynthesis genes is orchestrated during development or modulated by folate levels. Nor is much known about how folate levels impact the expression of other genes. These points were addressed using wild-type tomato fruit and fruit engineered for high folate content. In wild-type fruit, the expression of genes specifying early steps in folate biosynthesis declined during development but that of other gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 57 publications
0
36
1
Order By: Relevance
“…These observations are markedly different from those reported in tomato and rice (Storozhenko et al, 2007; Waller et al, 2010). Therefore, probably there is a bottleneck in the folate biosynthesis pathway in potato tubers, and a further research is needed to investigate the mechanisms of regulating folate status in these plants that are different, lacking, or of minor importance in rice seeds and tomato fruit.…”
Section: Manipulation Of Vitamin Metabolismcontrasting
confidence: 99%
“…These observations are markedly different from those reported in tomato and rice (Storozhenko et al, 2007; Waller et al, 2010). Therefore, probably there is a bottleneck in the folate biosynthesis pathway in potato tubers, and a further research is needed to investigate the mechanisms of regulating folate status in these plants that are different, lacking, or of minor importance in rice seeds and tomato fruit.…”
Section: Manipulation Of Vitamin Metabolismcontrasting
confidence: 99%
“…A limited number of regulated transcripts (fourteen) was also reported by Waller et al . [38] in a work on the expression of folate biosynthesis genes during tomato fruit development, demonstrating how tomato fruit pathways are finely regulated.…”
Section: Discussionmentioning
confidence: 99%
“…We in fact followed the plant development till the fruit formation, and focused our attention on the fruit transcriptome by performing a microarray experiment to determine the gene expression profiles in the fruits from mycorrhizal plants. Our transcriptomic analysis was based on the TOM2 oligo-array, which contains about 12000 unigenes, and which is estimated to include about half the genes expressed in fruit [38]. We demonstrate that only a limited number of genes were differentially regulated in the fruit from mycorrhizal plants, most of which were involved in ripening and N metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…3 years later, the same research team reported a 25-fold increase in folate accumulation in transgenic tomato fruits (de la Garza et al 2007). On the other hand, Waller et al (2010) showed that in engineered fruit overexpressing foreign GTP cyclohydrolase I and aminodeoxychorismate synthase genes, the expression of endogenous genes was not changed, but those of three downstream pathway genes, aminodeoxychorismate lyase, dihydroneopterin aldolase and mitochondrial folylpolyglutamate synthase, increased by up to 7.8-, 2.8-, and 1.7-fold respectively, apparently in response to the build-up of specific folate pathway metabolites.…”
Section: Improvement Of Fruit Qualitymentioning
confidence: 99%